The Host Cell Transcription Factor EGR1 Is Induced by Bacteria through the EGFR–ERK1/2 Pathway - de Klerk, Nele; Saroj, Sunil D.; Wassing, Gabriela M.; Maudsdotter, Lisa; Jonsson, Ann-Beth (Frontiers in Cellular and Infection Microbiology, 2017)
The essential first step in bacterial colonization is adhesion to the host epithelial cells. The early host-responses post-bacterial adhesions are still poorly understood. Early growth response 1 (EGR1) is an early response transcriptional regulator that can be rapidly induced by various environmental stimuli. Several bacteria can induce EGR1 expression in host cells, but the involved bacterial characteristics and the underlying molecular mechanisms of this response are largely unknown. Here, we show that EGR1 can be induced in host epithelial cells by different species of bacteria independent of the adherence level, Gram-staining type and pathogenicity. However, bacterial viability and contact with host cells is necessary, indicating that an active interaction between bacteria and the host is important. Furthermore, the strongest response is observed in cells originating from the natural site of the infection, suggesting that the EGR1 induction is cell type specific. Finally, we show that EGFR – ERK1/2 and β1-integrin signaling are the main pathways used for bacteria-mediated EGR1 upregulation. In conclusion, the increase of EGR1 expression in epithelial cells is a common stress induced, cell type specific response upon host-bacteria interaction that is mediated by EGFR – ERK1/2 and β1-integrin signaling.